2023
DOI: 10.3390/ma16020862
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Potential of a Polyethylene Glycol Hydrogel Functionalized with Poly-Lysine Dendrigrafts (DGL) for Bone Regeneration

Abstract: Resorbable hydrogels are widely used as scaffolds for tissue engineering. These hydrogels can be modified by grafting dendrimer-linked functionalized molecules (dendrigrafts). Our aim was to develop a tunable poly(L-lysine) dendrigrafts (DGL)/PEG-based hydrogel with an inverse porosity and to investigate its osteogenic potential. DGL/PEG hydrogels were emulsified in a surfactant-containing oil solution to form microspheres. The toxicity was evaluated on Human Vascular Endothelial Cells (HUVECs) and Bone Marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Roumani et al conducted a study in which they developed hydrogels based on L-lysine dendrimer graft (DGL) and PEG with adjustable polymerization of reverse porosity. This modified hydrogel demonstrated the ability to enhance the interaction between endothelial cells and hMSCs, thereby increasing osteogenic potential [ 59 ]. Synthetic polymer hydrogels show great promise as carriers for delivering active proteins, growth factors, and drugs to bone tissue.…”
Section: Hydrogel Materialsmentioning
confidence: 99%
“…Roumani et al conducted a study in which they developed hydrogels based on L-lysine dendrimer graft (DGL) and PEG with adjustable polymerization of reverse porosity. This modified hydrogel demonstrated the ability to enhance the interaction between endothelial cells and hMSCs, thereby increasing osteogenic potential [ 59 ]. Synthetic polymer hydrogels show great promise as carriers for delivering active proteins, growth factors, and drugs to bone tissue.…”
Section: Hydrogel Materialsmentioning
confidence: 99%
“…Testing by murine line L929 fibroblast cells revealed that they may be readily encapsulated in the gel matrix [ 142 ]. A very recent study published in 2023 also describes microspheres of hydrogels from Poly(L-lysine) dendrigrafts and PEG-bis(N-succinimidyl succinate) that can enhance osteogenic differentiation of Bone Marrow Mesenchymal Stem Cells [ 143 ].…”
Section: Dendritic Polymers Mediating To Cell Adhesion Proliferation ...mentioning
confidence: 99%
“…To further promote bone regeneration, poly-L-lysine (PLL) and fibronectin (FN), which are constituents of the extracellular matrix (ECM), have been shown to improve osteoblast adhesion within the scaffold, showing osteoconductive properties [20][21][22][23], and to promote cell differentiation and the interaction of scaffolds with mesenchymal stem cells, resulting in an enhanced osteogenic potential [22,24]. PLL and FN represent promising molecules for tissue engineering [25,26], to be better explored in composite scaffolds intended for the bone regeneration of critical-size defects.…”
Section: Introductionmentioning
confidence: 99%